Root canal treatment with calcium hydroxide. I. Effect of overfilling and refilling - Holland, R.; Nery, M. J.; de Mello, W.; de Souza, V.; Bernabé, P. F.E.; Filho, J.A.Otoboni (Elsevier, 1979)
Root canals of dog premolar teeth were negotiated and overfilled with calcium hydroxide paste. After 30 days, half of the treated teeth were refilled up to the apical limit. Root canals not filled were considered as the control group. Ninety days after the first treatment, histologic analysis showed more favorable results in the refilled root canals. The overfilling elicits calcium hydroxide resorption and the ingrowth of periapical connective tissue into the root canal. © 1979.